2022
DOI: 10.1007/s11142-022-09705-0
|View full text |Cite
|
Sign up to set email alerts
|

What can we learn about credit risk from debt valuation adjustments?

Abstract: Motivated by the debate about the introduction of the fair value option for (financial) liabilities (FVOL) and the requirement to recognize and separately disclose in financial statements debt valuation adjustments (DVAs), this study explores what we can learn about a firm’s credit risk from DVAs. Using a sample of US bank holding companies that elect the FVOL, we show that DVAs generally cannot be explained by the same factors that explain contemporaneous changes in bank’s credit quality. We further find that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Second, the estimation of DVA involves significant data observability and analytical difficulties discussed in section ''Background and Related Literature'' that limit the ability of auditors, supervisors, investors, and other outsiders to discipline banks' exercise of discretion over DVA. Consistent with this point, Lin et al (2019) posit that managers have superior private information about banks' own credit risk, and they provide evidence that DVA measured using Level 3 (unobservable) inputs predicts banks' future credit risk changes, but that DVA measured using Level 1 and 2 (observable) inputs does not.…”
Section: Hypothesesmentioning
confidence: 65%
See 1 more Smart Citation
“…Second, the estimation of DVA involves significant data observability and analytical difficulties discussed in section ''Background and Related Literature'' that limit the ability of auditors, supervisors, investors, and other outsiders to discipline banks' exercise of discretion over DVA. Consistent with this point, Lin et al (2019) posit that managers have superior private information about banks' own credit risk, and they provide evidence that DVA measured using Level 3 (unobservable) inputs predicts banks' future credit risk changes, but that DVA measured using Level 1 and 2 (observable) inputs does not.…”
Section: Hypothesesmentioning
confidence: 65%
“…They conclude that DVA gains and losses are counterintuitive only when banks do not report more than offsetting losses and gains on assets. 5 Lin et al (2019) find that DVA reported by U.S. banks selecting FVO for financial liabilities during the period 2007 to 2017 cannot be fully explained by market-based credit risk measures such as CDS or bond spreads. They provide evidence that banks’ DVA measured using Level 3 (unobservable) inputs explains future changes in their CDS spreads, consistent with bank managers having greater ability than market participants to estimate their banks’ own credit risk.…”
Section: Background and Related Literaturementioning
confidence: 96%